Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1021/ac020477o
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interfacial Refractive Index on Optical Molecular Orientation Measurements

Abstract: The sensitivity of optical molecular orientation measurements to assumptions regarding thin film refractive index was investigated. Specifically, the influence of the interfacial refractive index on second harmonic generation (SHG) and linear dichroism measurements made in a total internal reflection (TIR) geometry was probed for five distinct molecular systems. The five molecular thin films ranged from weakly adsorbed species in equilibrium with solution to covalently bound molecules. Polarization data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…37,42 There are also efforts trying to show that the dielectric constant of the extremely thin monolayer is just the simple arithmetic average of the two bulk dielectric constants. 52,58,67,68 Event though the results from these approaches seemed reasonable, neglecting the anisotropic microscopic local field effect in the molecular monolayer is not likely to be physically sound.…”
Section: 64mentioning
confidence: 99%
See 3 more Smart Citations
“…37,42 There are also efforts trying to show that the dielectric constant of the extremely thin monolayer is just the simple arithmetic average of the two bulk dielectric constants. 52,58,67,68 Event though the results from these approaches seemed reasonable, neglecting the anisotropic microscopic local field effect in the molecular monolayer is not likely to be physically sound.…”
Section: 64mentioning
confidence: 99%
“…42,52,58,67,68,69,70,71 In SFG-VS, some considered the film anisotropic and its optical constant is determined using the Clausius-Mossotti relationship with the ellipsometry data of the film.…”
Section: 64mentioning
confidence: 99%
See 2 more Smart Citations
“…38,39,40 However, researchers have long realized that the crucial issues in the quantitative interface studies with the SHG and SFG are on how to describe the macroscopic dielectric constant of the molecularly thin layer and how to calculate the anisotropic two dimensional microscopic local field effect. 21,25,41,42,43,44,45,46,47,48,49,50,51,52,53 It has been well demonstrated that in majority cases the calculation of the molecular orientation is quite sensitive to the values used for these two factors. 21,25,42,51,52 In the currently accepted models of the nonlinear optics of interface, 4,34,41,53,54,55 the nonlinear radiation was treated as the result of an infinitesimally thin polarization sheet layer, and as the starting pint a macroscopic dielectric constant was assigned to this thin layer.…”
Section: Introductionmentioning
confidence: 99%